Green bonds as hedging assets before and after COVID - Guo, Dong,Zhou, Peng (Cardiff Business School, Cardiff University, 2021)
The COVID pandemic reveals the fragility of the global financial market during rare disasters. Conventional safe-haven assets like gold can be used to hedge against ordinary risks, but tail dependence can substantially reduce the hedging effectiveness. In contrast, green bonds focus on long-term, sustainable investments, so they become an important hedging tool against climate risks, financial risks, as well as rare disasters like COVID. The copula approach based on the TGARCH model is applied to estimate the joint distributions between green bonds and selected financial assets in both US and China. The quantile-based approach is also performed to offer a robustness check on tail dependence. The results show that all assets in the two countries have thick tails and tail dependence with time-varying features. The hedging effectiveness does decline during the COVID pandemic, but it is the hedging effectiveness against tail risks rather than against normal risks. It is argued that green bonds play a significant role in hedging against rare disasters especially in forex markets. It is also found that green bonds in the US and China converge in many aspects, suggesting a smaller cross-country difference than cross-asset difference.
10419/261221
Keywords: Graue Literatur; green bonds; hedging effectiveness; COVID